Research and technology organizations as entrepreneurship instruments: The case of the Institut National d'Optique in the Canadian optics and photonics industry - Mahdi Khelfaoui; Luc Bernier (Journal of Innovation and Entrepreneurship, 2023)
Research and technology organizations (RTOs) are studied in the innovation policy literature mainly as providers of R&D services and as intermediaries between universities and the private sector. Through the case of the Institut National d'Optique (INO), Canada's leading RTO in the optics and photonics industry, we argue that RTOs can also act as entrepreneurs by generating technologies and commercializing them through licensing, technology transfers and spin-offs. By analyzing the broad range of activities undertaken by INO, we also discuss what characteristics make some RTOs more likely to embrace entrepreneurship than others. Those characteristics include the following: renewed access to government funding to build a strong in-house research infrastructure and scientific workforce; strategic R&D planning that incorporates commercial objectives and an environment that encourages a culture of entrepreneurship among employees; the ability to act as the driving force of a network of academic, government and private sector organizations. From a policy perspective, the INO case indicates that the main value of using RTOs as entrepreneurship instruments does not lie in profitability but rather in developing dynamic regional systems of innovation.
Keywords: 650; Innovation; Entrepreneurship; Technology transfer; RTO; Spin-offs